The informational role of thin options markets: Empirical evidence from the Spanish case - García Martín, C. José; Herrero Piqueras, Begoña; Ibañez Escribano, Ana María (Estudios de Economía, 2016)
This study investigates the informational role of thin options markets, specifically the Spanish options market. Firstly, we examine the effect of options markets by analysing stock market reaction to earnings news, conditional on the availability of options markets. Secondly, we examine options trading activity before the release of earnings news (including the announcement period). The results show that the impact on prices before the earnings release is significantly bigger when options trading is available. Moreover, the dissemination of earnings news is associated with significant unusual activity in the options market due to informed trading, especially when the earnings surprise is highly good.